2010
DOI: 10.1111/j.1750-3841.2010.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Disinfection Mechanism of Electrolyzed Oxidizing Water on E. coli and Staphylococcus aureus

Abstract: The effectiveness of using protease and combinations of protease and high-intensity ultrasound for high-purity, high-yield tamarind seed polysaccharide (TSP) production was investigated. Tamarind kernel powder (TKP) suspension was treated with protease alone at 0.16, 0.48, and 0.80 units/mL and with protease-ultrasound combinations over 3 different orders of sequence (before, simultaneous with, and after protease digestion) using combinations of 0.48 units/mL protease and high-intensity ultrasound at 25% and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 24 publications
4
57
0
Order By: Relevance
“…The results showed that lactic acid could damage the membranes of Salmonella, E. coli and Listeria, resulting in an unbalanced osmotic pressure between intracellular and extracellular ionic concentrations (Zeng et al, 2010). Eventually, the large leakage of K þ led to a great lack of intracellular K þ , which could influence the intracellular physiological functions and even result in the bacterial mortality (Marklund, Behnam-Motlagh, Henriksson, & Grankvist, 2001).…”
Section: Release Of Intracellular Potassium (K þ )mentioning
confidence: 98%
“…The results showed that lactic acid could damage the membranes of Salmonella, E. coli and Listeria, resulting in an unbalanced osmotic pressure between intracellular and extracellular ionic concentrations (Zeng et al, 2010). Eventually, the large leakage of K þ led to a great lack of intracellular K þ , which could influence the intracellular physiological functions and even result in the bacterial mortality (Marklund, Behnam-Motlagh, Henriksson, & Grankvist, 2001).…”
Section: Release Of Intracellular Potassium (K þ )mentioning
confidence: 98%
“…Setlow et al 2002 reported that the disinfection mechanism of strong acid or alkali treatment on Bacillus subtilis spores was due to the inactivation of the intracellular enzymes and the disruption of the permeability barrier. To date only a few researchers have investigated the disinfection mechanism of electrolyzed oxidizing water (EOW) (Zeng et al, 2010(Zeng et al, , 2011. These researchers reported that EOW caused damage to the cell walls, nucleus and outer membranes, which lead to the rapid leakage of intracellular K þ , DNA and proteins, and a decrease in the dehydrogenase activities of S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have addressed the mechanism of microbial inactivation by EW. These include the increase of membrane permeability together with leakage of cellular components and the decrease of activity of several key enzymes in bacteria such as E. coli and Staphylococcus aureus (Liao et al 2007;Zeng et al 2010) as well as the yeast Candida albicans . Degradation of chromosomal DNA has been also observed in Pseudomonas aeruginosa (Kiura et al 2002) and cause aggregation of essential bacterial proteins (Winter et al 2008) or interfering bacteria cell protein composition (Cloete et al 2009).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%